THE ROLE OF AI-ASSISTED LEARNING IN ENHANCING CRITICAL THINKING AND REFLECTIVE TEACHING PRACTICES IN FUTURE ENGLISH TEACHERS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Artificial Intelligence (AI) is transforming teacher education by providing innovative tools that support critical thinking and reflective teaching. This article examines the role of AI-assisted learning in developing these essential skills among future English teachers.